Pengaruh Affiliate Marketing dan Live Streaming Terhadap Keputusan Pembelian Shopee di Komplek TNI-AU Flamingo Medan - Ayu, Younda Dwi; Siregar, Muhammad Yamin; Rafiki, Ahmad (Economics, Business and Management Science Journal, 2025)
The purpose of this study was to determine the business capital, labor and pond area partially and simultaneously affect the income of the Carp business in Lawe Pangkat Village, Deleng Pokhkisen District, Southeast Aceh Regency in Lawe Pangkat Village. The population in this study were people who had a Carp business in Lawe Pangkat Village, Deleng Pokhkisen District, Southeast Aceh Regency in Lawe Pangkat Village as many as 50 people. The sample in the study was 50 people obtained using saturated samples. The data collection technique used in this study was carried out by distributing questionnaires. The analysis technique used in this study was multiple linear regression, partial test (t-test), simultaneous significance test (F-test) and coefficient of determination. The results showed that business capital, labor and pond area had a positive and significant effect partially and simultaneously on the income of the Carp business in Lawe Pangkat Village, Deleng Pokhkisen District, Southeast Aceh Regency in Lawe Pangkat Village. Based on the determination coefficient test (R2) shows that the Adjusted R Square value of 0.562% means that business capital, labor and pond area affect business income by 56.2% and the remaining 43.8% are other variables not examined by this study, such as experience, entrepreneurial ability and other variables.